Multi-Resolution Denoising for Foveated Rendering Path Tracing - Silva, Leonardo Noia Nanci de Araujo; Henriques, Horácio Brescia Macedo; Porcino, Thiago; Montenegro, Anselmo Antunes; Clua, Esteban W. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Path tracing rendering algorithms present a significant challenge for interactive applications due to the high sample counts required per pixel to achieve low-variance images. To mitigate this issue, denoising techniques have been developed to reduce computational costs by predicting the fully converged render from noisy images generated with fewer samples per pixel. This challenge is exacerbated when rendering for head-mounted displays, where the proximity of the user’s eyes to the screen increases computational demands. However, this proximity can be leveraged to reduce the time required to generate the final image. In this study, we propose a method for accelerating path tracing rendering specifically designed for extended reality (XR) devices. Our approach incorporates multi-resolution foveated rendering techniques combined with multi-pass nonhomogenous denoising strategies for different image regions. Experimental results in testing scenarios with high triangle counts demonstrate significant improvements in both image quality and acceleration rates, rendering frames three times faster than standard path tracing strategies.